Effect Of Employee Productivity Firm Size And Board Size On Intellectual Capital Performance With Profitability As Moderating Variable - Putu Gede Wisnu Permana KAWISANA; L.G.P Sri Eka JAYANTI (Indonesia Strategic Sustainability, 2021)
Based on data from the Central Statistics Agency (BPS), the economy measured by gross domestic product at current prices reached Rp. 15,833.9 trillion and GDP per capita of 4174.9. Economic growth in the fourth quarter of 2019 reached 5.02%, down from 5.17% in 2018. This study aims to determine and analyze the effect of employee productivity, company size, board size on intellectual capital performance in companies incorporated in the LQ index. -45. The number of samples obtained in this company is as many as 97 with purposive samples as a method of determining the sample. In addition, the main purpose of this study is to find out and analyze whether profitability can moderate the effect of employee productivity on company size, board size on intellectual capital performance in companies that are included in the LQ-45 index. The research method in this study is a quantitative method by analyzing the annual financial statements of companies listed on the Indonesia Stock Exchange. The results of this study prove that the profitability variable is able to moderate the relationship between employee productivity, company size, and intellectual capital performance. Profitability, meanwhile, is unable to moderate the relationship between board size and intellectual capital performance.